Tahapan Perkembangan Provinsi DKI Jakarta Menuju Smart City - Tommy Kurnia; Achmad Djunaedi (TATALOKA, 2020)
The success of DKI Jakarta Province in implementing the concept of smart city has led DKI Jakarta Province to receive various awards both at national and international levels. This situation shows that its urban management is already well developed, even though DKI Jakarta Province is faced with various complex problems. Also, up to now in the literature there is no clear concept regarding the process of developing smart cities, especially in cities with national capital status. Therefore, this study aims to describe the stages of the development of the Province of DKI Jakarta towards smart city and identify what factors influence it. This research was conducted with a qualitative approach and exploratory case study method, while data were analyzed through time series analysis. The results of this study state that there are 4 stages in the development of DKI Jakarta Province towards smart cities, namely: phase 1 E-Government, phase 2 Open Data Government, stage 3 Underpinning Smart City and stage 4 Implementing Smart City. The stages starting from 2003 to 2018 involving the implementation of e-government, public information disclosure, the principle of good governance and starting the implementation of Smart City. The research identified 19 factors influencing the stages of the development of DKI Jakarta Province towards Smart City which is further divided into four categories of factors namely globalization, regional position, governance and stakeholder collaboration.